PERAN KOMPETENSI DAN ETIKA AUDITOR DALAM MENINGKATKAN KUALITAS AUDIT - Hanafi, Reza; Tasya Marshanda, Cut; Sahputri Siregar, Alya; Syahara, Mutia; Dwi Ningrum, Silvi; Mahdalia, Desy (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
Audit quality plays a crucial role in ensuring the reliability of financial reports and maintaining public trust in the audit profession. Various weaknesses in the audit process, discrepancies in findings between auditors, and ethical violations indicate that audit quality still requires serious attention. Through a literature review reviewing several national and international journals, this study outlines how auditor competence and ethics contribute to improving audit quality. The study's findings indicate that competence, encompassing technical ability, experience, and professional training, strongly influences auditor accuracy in assessing risks and detecting material errors. Meanwhile, auditor ethics, including integrity, objectivity, independence, and professional responsibility, serve as the primary foundation for maintaining honesty and transparency in audit implementation. Audit quality will achieve its best results when competence and ethics are applied in a balanced manner, as weaknesses in either aspect can compromise audit reliability. This study emphasizes the need for improved professional training and strengthened implementation of codes of ethics to support high-quality audits that gain public trust.